2010
DOI: 10.1007/s00222-010-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

The asymptotic distribution of Frobenius numbers

Abstract: Abstract. The Frobenius number F (a) of an integer vector a with positive coprime coefficients is defined as the largest number that does not have a representation as a positive integer linear combination of the coefficients of a. We show that if a is taken to be random in an expanding d-dimensional domain, then F (a) has a limit distribution, which is given by the probability distribution for the covering radius of a certain simplex with respect to a (d − 1)-dimensional random lattice. This result extends rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 20 publications
5
94
0
8
Order By: Relevance
“…That is, the set E R = {L ∈ Ω 0 : Q 0 (L) = R} is contained in a union of finitely many bounded connected submanifolds of Ω 0 of strictly lower dimension. In fact the statement is "almost" established in [M10,Lemma 7], and we will provide some further explanation of the results there. In view of Remark 4.11, our Theorem 1.4 can be deduced with essentially the same argument as in Proposition 4.12 .…”
Section: Proof Of Theorem 14supporting
confidence: 59%
See 1 more Smart Citation
“…That is, the set E R = {L ∈ Ω 0 : Q 0 (L) = R} is contained in a union of finitely many bounded connected submanifolds of Ω 0 of strictly lower dimension. In fact the statement is "almost" established in [M10,Lemma 7], and we will provide some further explanation of the results there. In view of Remark 4.11, our Theorem 1.4 can be deduced with essentially the same argument as in Proposition 4.12 .…”
Section: Proof Of Theorem 14supporting
confidence: 59%
“…In the proof of [M10,Lemma 7], it is shown that (4.15) (4.14) ⊆ {A = (a ij ) ∈ G 0 : tr(LA) = R} , where L is the (n − 1) × (n − 1) matrix whose i-th column is n i − n d . Because L R is a relatively compact , there is a constant C R > 0, so that (4.15) can be refined to (4.16) (4.14) ⊆ {A = (a ij ) ∈ G 0 : |a ij | < C R , tr(LA) = R} .…”
Section: Proof Of Theorem 14mentioning
confidence: 99%
“…The hardest case of this problem concerns the case d = 3 and was resolved by Duke [Duk88] (building on a breakthrough of Iwaniec [Iwa87]). Following Maass [Maa56,Maa59] and W. Schmidt [Sch98] (see also [Mar10] Finally we note k v SO d−1 (R) is uniquely defined by the above requirement on k v and hence [Λ v ] is canonically attached to the vector v. We refer to [Λ v ] as the shape of the lattice associated to v.…”
Section: Introductionmentioning
confidence: 99%
“…The limiting distribution of F(a) in the 3-dimensional case was derived in Shur, Sinai, and Ustinov [38], and for the general case, see Marklof [30]. Upper bounds for the average value of F(a) have been obtained in Aliev and Henk [5] and Aliev, Henk and Hinrichs [6].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%